Effect of Intravenous 25OHD Supplementation on Bone Turnover and Inflammation in Prolonged Critically Ill Patients - Ingels, Catherine; Vanhorebeek, Ilse; Van Cromphaut, Sophie; Wouters, Pieter J.; Derese, Inge; Dehouwer, Alexander; Møller, Holger Jon; Hansen, Troels K.; Billen, Jaak; Mathieu, Chantal; Bouillon, Roger; Van den Berghe, Greet (Hormone and Metabolic Research, 2020)
Critically ill patients have low circulating 25-hydroxyvitamin D (25OHD), vitamin D binding protein (DBP), and 1,25-dihydroxyvitamin D [1,25(OH)2D]. Low 25OHD is associated with poor outcomes, possibly explained by its effect on bone and immunity. In this prospective, randomized double-blind, placebo-controlled study, we investigated the feasibility of normalizing 25OHD in prolonged (>10 days) critically ill patients and the effects thereof on 1,25(OH)2D, bone metabolism, and innate immunity. Twenty-four patients were included and compared with 24 matched healthy subjects. Patients were randomized to either intravenous bolus of 200 μg 25OHD followed by daily infusion of 15 μg 25OHD for 10 days, or to placebo. Parameters of vitamin D, bone and mineral metabolism, and innate immune function were measured. As safety endpoints, ICU length of stay and mortality were registered. Infusion of 25OHD resulted in a sustained increase of serum 25OHD (from median baseline 9.2 –16.1 ng/ml at day 10), which, however, remained below normal levels. There was no increase in serum 1,25(OH)2D but a slight increase in serum 24,25(OH)2D. Mineral homeostasis, innate immunity and clinical safety endpoints were unaffected. Thus, intravenous 25OHD administration during critical illness increased serum 25OHD concentrations, though less than expected from data in healthy subjects, which suggests illness-induced alterations in 25OHD metabolism and/or increased 25OHD distribution volume. The increased serum 25OHD concentrations were not followed by a rise in 1,25(OH)2D nor were bone metabolism or innate immunity affected, which suggests that low 25OHD and 1,25OHD levels are part of the adaptive response to critical illness.
Keywords: vitamin D; critical illness; innate immunity; bone metabolism